2012
DOI: 10.1111/j.1365-2036.2012.05121.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between liver histology and novel magnetic resonance imaging in adult patients with non‐alcoholic fatty liver disease – MRI accurately quantifies hepatic steatosis in NAFLD

Abstract: SUMMARY Background Conventional magnetic resonance imaging (MRI) techniques that measure hepatic steatosis are limited by T1 bias, T2* decay and multi-frequency signal-interference effects of protons in fat. Newer MR techniques such as the proton density-fat fraction (PDFF) that correct for these factors have not been specifically compared to liver biopsy in adult patients with non-alcoholic fatty liver disease (NAFLD). Aim To examine the association between MRI-determined PDFF and histology-determined stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
283
2
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(303 citation statements)
references
References 24 publications
5
283
2
8
Order By: Relevance
“…The advantage of magnetic resonance imaging-proton-derived fat fraction (MRI-PDFF) over previous methods is that it gives a global assessment of liver fat, whereas techniques, such as MR spectroscopy, measure fat from regions of interest within the liver, which can be associated with sampling variability [26]. Recent cross-sectional studies have shown that PDFF correlates well with histological assessment of steatosis (r 2 = 0.54, p < 0.001 and r 2 = 0.69, p < 0.001, respectively) [25,27] and can accurately distinguish between the presence or absence of hepatic steatosis (AUROC of 0.989) [25]. MRI-PDFF also had good inter-examination accuracy for whole liver assessment (ICC = 0.999; SD < 0.24%, range < 0.45%) [28].…”
Section: Magnetic Resonance Imaging-proton-derived Fat Fraction (Mri mentioning
confidence: 82%
“…The advantage of magnetic resonance imaging-proton-derived fat fraction (MRI-PDFF) over previous methods is that it gives a global assessment of liver fat, whereas techniques, such as MR spectroscopy, measure fat from regions of interest within the liver, which can be associated with sampling variability [26]. Recent cross-sectional studies have shown that PDFF correlates well with histological assessment of steatosis (r 2 = 0.54, p < 0.001 and r 2 = 0.69, p < 0.001, respectively) [25,27] and can accurately distinguish between the presence or absence of hepatic steatosis (AUROC of 0.989) [25]. MRI-PDFF also had good inter-examination accuracy for whole liver assessment (ICC = 0.999; SD < 0.24%, range < 0.45%) [28].…”
Section: Magnetic Resonance Imaging-proton-derived Fat Fraction (Mri mentioning
confidence: 82%
“…MRI-PDFF has been shown to be a highly precise, accurate, and reproducible noninvasive biomarker for the quantification of liver fat content (41,42). It has been proven to correlate well with magnetic resonance spectroscopy (r 2 = 0.99, P < 0.001) (30,43) and histology-proven steatosis grade from contemporaneous liver biopsies (36,40), and it is superior to ultrasound and CT for quantification of liver fat content (44). Rationale for using MRE-stiffness for hepatic fibrosis quantification.…”
Section: Methodsmentioning
confidence: 99%
“…MRI-PDFF was used to measure hepatic steatosis, and MRE was used to measure hepatic fibrosis. The details of the MRI protocol have been previously described in references (31,40). The image analysts were blinded to all clinical and biochemical data, including the study group of the participants.…”
Section: Methodsmentioning
confidence: 99%
“…[Au: Some information moved to the figure legend.] In numerous single-centre and multi-centre studies, PDFF has shown high accuracy for diagnosing, grading, and longitudinally monitoring steatosis in adults and children, including morbidly obese individuals [142][143][144][145][146][147] .…”
Section: [H2] Epigeneticsmentioning
confidence: 99%